Comparative Study of Seismic Behavior between Monolithic Precast Concrete Structure and Cast-in-Place Structure - Chao-gang Qin; Guo-liang Bai; Ya-zhou Xu; Ning-fen Su; Tao Wu (Shock and Vibration)
We doubt whether the monolithic precast concrete structure could be designed as the cast-in-place structure in high seismic intensity area. To solve the puzzle, the 1/5 scaled monolithic precast concrete structure model and cast-in-place structure model were designed and tested by shake table. Comparative analysis between them was made to better understand their seismic behavior. Based on the experimental results, the failure pattern and mechanism were different, which was concentrated damage in coupling beam and then extended to shear walls of CIPS, and the weak connections presented cracks between precast elements besides the damage coupling beam of MPCS. The natural frequency of MPCS possessed a typical feature for the weakness of connections, which was the initial one greater than that of CIPS and decreased fast after the first waves with PGA of 0.035 g. Acceleration amplifying factors presented variation trend under the different earthquake waves. The distribution of seismic response presented linearity along the height of models in plastic stage and turned into nonlinearity later for severe damage. In general, the MPCS and CIPS had similar seismic responses, except typical characteristics. And they were proven to have better seismic performance without collapse under the high-intensity earthquake waves.